FITTING IDEAL DAN PENGARUHNYA TERHADAP KESTABILAN LENSA KONTAK LUNAK TORIK - Darma Kusumah; Murni Marlina Simarmata; Ferry Doringin (Jurnal Mata Optik, 2020)
Toric soft contact lenses are contact lenses that have silinderstrength so they can be used to correct astigmatism disorders. The difference in meridian strength involves a difference in thickness that affects the stability of the toric soft contact lens that is attached to the eye. One of the problems most frequently complained of by users of toric soft contact lenses is unstable visual acuity where when the soft toric contact lens is used the vision becomes unclear due to the soft toric contact lens that is attached to the eye rotating so that the axis shifts. This is often caused by the inaccuracy of contact lens Fitting that has not been carried out before trial installation, so conducting a trial first in recommending toric soft contact lenses is very important to ensure the stability of soft toric contact lenses when worn by users. This paper aims to determine and discuss that the ideal Fitting assessment greatly affects the stabilization of toric soft contact lenses.